Pengembangan Komoditi Unggulan Mengunakan Lokal Ekonomi Development di Kabupaten Flores Timur - Irada Subhan; Kendry Widyanto; Hasan Ismail (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2026)
The agriculture, plantation, and fisheries sectors are the mainstays of the economy in East Flores Regency. However, this region still faces socio-economic challenges such as high poverty rates, minimal employment opportunities, and low added value of the products produced. This study aims to analyze and describe the development strategy for superior agricultural commodities in East Flores Regency using the Local Economic Development (LED) approach. The LED approach emphasizes the importance of optimizing internal capacity and participatory partnerships between local actors to encourage inclusive and sustainable economic growth. This study uses a qualitative approach with a descriptive research type. Data collection was conducted through field observations, documentation, and in-depth interviews with informants from Bapprida, the Manpower Office, the Plantation and Livestock Office, Village Heads, business actors, and local farmers. Data analysis was applied with reference to the interactive model of Miles, Huberman, and Saldaña. Data validity and the focus of the study are based on the four main dimensions of LED according to Edward J. Blakely’s theory: locality, business and economic base, employment resources, and community resources. The research results show that East Flores Regency has a strong local economic foundation, with coconut, cocoa, coffee, and cashew nuts serving as the backbone of community activities. However, in terms of locality, productivity remains hampered by limited basic infrastructure, particularly access to clean water in dryland areas. In terms of business and economic base, the management of leading commodities has not been optimal in creating added value due to dependence on the traditional primary sector and weak policy integration. In terms of employment resources, the availability of a productive-age workforce is abundant, but skills capacity and employment opportunities in the productive sector remain very limited, triggering a high number of workers migrating out of the region. Meanwhile, in terms of community resources, social capital in the form of farmer groups and local wisdom is very strong, but its function remains administrative and has not yet transformed into a highly competitive business force. It can be concluded that the development of leading commodities based on LED in East Flores Regency is at a developing stage but requires significant strengthening. The local government needs to build consistent cross-sectoral synergy, accelerate the distribution of basic infrastructure, and improve post-harvest skills training programs for farmer groups to achieve equitable community welfare.